CPSC 359: Tutorial 2

 

PhD Student

Fall 2018

Today

More exercises related to algebraic minimization

So what are the tools we have for minimization?

Theorems

a) b)
Postulate 2 x+0 = x x*1 = x
Postulate 5 x+x' = 1 x*x' = 0
Theorem 1 x + x = x x*x = x
Theorem 2 x+1 = 1 x*0 = 0
Theorem 3 (x')' = x
Theorem 4 x+y=y+x xy=yx
Theorem 4 x+(y+z)=(x+y)+z (xy)z=x(yz)
Theorem 5 (x+y)' = x'y' (xy)' = x' + y'
Theorem 6 x+xy = x x(x+y) = x

An approach to minimization is to factor out terms like (x' + x) or x'x

Boolean Functions

\(f=x+y\cdot z\)

The goal of this tutorial is to get you familliar with boolean functions, i.e.

\(x\)

\(z\)

\(y\)

\(f\)

We'll look at a couple of these as examples

Theorems

In the original slide deck I forgot the absorption law

\(x + (x\cdot y) = x\)    (OR Absorption Law)

\(x\cdot (x + y) = x\)    (AND Absorption Law)

Algebraic Simplification

Recall the function from last tutorial

\(f=x+y^\prime+z^\prime+yz\)

We reasoned that \(f=1\) by the truth table, but how do we see it via algebraic manipulation?

Exercises

Algebraically minimize the following function, then create a truth table for both functions to show they're equivalent

\(f=x+x'y\)

a) b)
Postulate 2 x+0 = x x*1 = x
Postulate 5 x+x' = 1 x*x' = 0
Theorem 1 x + x = x x*x = x
Theorem 2 x+1 = 1 x*0 = 0
Theorem 3 (x')' = x
Theorem 4 x+y=y+x xy=yx
Theorem 4 x+(y+z)=(x+y)+z (xy)z=x(yz)
Theorem 5 (x+y)' = x'y' (xy)' = x' + y'
Theorem 6 x+xy = x x(x+y) = x

Exercises

Algebraically minimize the following function, then create a truth table for both functions to show they're equivalent

\(f=xy + x'z+yz\)

a) b)
Postulate 2 x+0 = x x*1 = x
Postulate 5 x+x' = 1 x*x' = 0
Theorem 1 x + x = x x*x = x
Theorem 2 x+1 = 1 x*0 = 0
Theorem 3 (x')' = x
Theorem 4 x+y=y+x xy=yx
Theorem 4 x+(y+z)=(x+y)+z (xy)z=x(yz)
Theorem 5 (x+y)' = x'y' (xy)' = x' + y'
Theorem 6 x+xy = x x(x+y) = x

Complement of a Function

\(f=xy + x'z+yz\)

At times, it's useful to take the compliment of a function, i.e.

\(f'=(xy + x'z+yz)'\)

Two "methods" for distributing the negation, DeMorgan's and the short cut method.

Short Cut Method

\(f=xy + x'z+yz\)

DeMorgan's Theorem is straight forward to use, but a bit tedious, so we have the "short cut method". i.e

(x+y)(x'+z)(y+z)

  1. Form the dual (ands become ors, ors become ands)
  2. Negate each literal

f=(x'+y')(x+z')(y'+z')

Exercises

Use both DeMorgan's rule and the shortcut method to calculate the complement of 

\(f=(x'yz' + x'y'z)'\)

a) b)
Postulate 2 x+0 = x x*1 = x
Postulate 5 x+x' = 1 x*x' = 0
Theorem 1 x + x = x x*x = x
Theorem 2 x+1 = 1 x*0 = 0
Theorem 3 (x')' = x
Theorem 4 x+y=y+x xy=yx
Theorem 4 x+(y+z)=(x+y)+z (xy)z=x(yz)
Theorem 5 (x+y)' = x'y' (xy)' = x' + y'
Theorem 6 x+xy = x x(x+y) = x

Exercises

Use both DeMorgan's rule and the shortcut method to calculate the complement of 

\(f=(x[y'z' +yz])\)'

a) b)
Postulate 2 x+0 = x x*1 = x
Postulate 5 x+x' = 1 x*x' = 0
Theorem 1 x + x = x x*x = x
Theorem 2 x+1 = 1 x*0 = 0
Theorem 3 (x')' = x
Theorem 4 x+y=y+x xy=yx
Theorem 4 x+(y+z)=(x+y)+z (xy)z=x(yz)
Theorem 5 (x+y)' = x'y' (xy)' = x' + y'
Theorem 6 x+xy = x x(x+y) = x

Next day

We'll look at Assignment 1, talk about what's expected and what's important to know.

Probably also canonical forms...

CPSC 359: Tutorial 2

By Joshua Horacsek

CPSC 359: Tutorial 2

  • 1,048